2020
DOI: 10.1504/ijmdm.2020.104208
|View full text |Cite
|
Sign up to set email alerts
|

Technology readiness and purchase intention: role of perceived value and online satisfaction in the context of luxury hotels

Abstract: This study investigates the relationships among customer technology readiness, perceived value, satisfaction with hotel website integrated self-service technologies, and purchase intention. The data for this study were collected from 668 international tourists who stayed in major cities' luxury hotels in Vietnam. Data were analysed using structural equation modelling technique. The results indicated that optimism and innovativeness positively influence customer perceived value, and insecurity negatively influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 61 publications
4
30
0
1
Order By: Relevance
“…The meaning of customer perceived value is constantly enriched in theory research. Pham et al (2020) found that perceived value was positively impacted by optimism and innovativeness, and insecurity had negatively effect on perceived value; customer satis-Journal of Service Science and Management faction and purchase intention were positively affected by perceived value. In the meanwhile customer satisfaction had positively influences on purchase intention.…”
Section: Perceived Value and Purchase Intentionmentioning
confidence: 96%
“…The meaning of customer perceived value is constantly enriched in theory research. Pham et al (2020) found that perceived value was positively impacted by optimism and innovativeness, and insecurity had negatively effect on perceived value; customer satis-Journal of Service Science and Management faction and purchase intention were positively affected by perceived value. In the meanwhile customer satisfaction had positively influences on purchase intention.…”
Section: Perceived Value and Purchase Intentionmentioning
confidence: 96%
“…The inconsistent findings have resulted in calls made to researchers to further investigate the use of the TR concept in various studies (Lundberg, 2017;Parasuraman & Colby, 2001); for instance, to make an assessment on whether TR has a relationship with technology usage (Blut & Wang, 2019); or to make an examination on whether individual's belief towards technology (such as TR) will influence their behavioural intention (Chiu & Cho, 2020). According to Pham et al (2020), there is a gap in the literature on the application of TR with technology usage intention (such as online purchase intention) with a lack of studies that examine the relations between TR and technology usage intention rather than actual adoption.…”
Section: Importance and Neglect Of Trmentioning
confidence: 99%
“…Blut and Wang's (2019) study, for example, found that an optimistic individual tends to concentrate on the positive perspective instead of the negative perspective of technology, resulting in the individual putting a higher value evaluation on new technology. According to Pham et al (2020), the optimism trait will assist people to believe in technology, to perceive the benefits provided by the technology, and to possess a sense of ease to use when it comes to technology. Furthermore, optimistic individual trusts that technology will grant a large number of values and useful functions for them to complete their job in the most efficient and effective way (Pham et al, 2020).…”
Section: Motivators Of Tr -Optimism and Innovativenessmentioning
confidence: 99%
See 2 more Smart Citations